Functional epistasis on a common MHC haplotype associated with multiple sclerosis. - Gregersen, J; Kranc, K; Ke, X; Svendsen, P; Madsen, L; Thomsen, A; Cardon, L; Bell, J; Fugger, L (2006)
Genes in the major histocompatibility complex (MHC) encode proteins important in activating antigen-specific immune responses. Alleles at adjacent MHC loci are often in strong linkage disequilibrium; however, little is known about the mechanisms responsible for this linkage disequilibrium. Here we report that the human MHC HLA-DR2 haplotype, which predisposes to multiple sclerosis, shows more extensive linkage disequilibrium than other common caucasian HLA haplotypes in the DR region and thus seems likely to have been maintained through positive selection. Characterization of two multiple-sclerosis-associated HLA-DR alleles at separate loci by a functional assay in humanized mice indicates that the linkage disequilibrium between the two alleles may be due to a functional epistatic interaction, whereby one allele modifies the T-cell response activated by the second allele through activation-induced cell death. This functional epistasis is associated with a milder form of multiple-sclerosis-like disease. Such epistatic interaction might prove to be an important general mechanism for modifying exuberant immune responses that are deleterious to the host and could also help to explain the strong linkage disequilibrium in this and perhaps other HLA haplotypes.